Design and Control of a Novel Multi-Degree-of-Freedom Spherical Induction Motor. Issue 12 (21st July 2023) - Ding, Zhentao; Deng, Tao; Su, Zhenhua; Wu, Changjun; Yin, Yanli
Abstract: To realize the omni-directional steering function of urban micro electric vehicle and avoid the defects of traditional multi-degree-of-freedom (multi-DOF) drive, a multi-DOF spherical induction motor (SIM) as hub motor is presented, which is used to replace the conventional wheel and steering system to drive vehicles directly. SIM is mainly composed of three arc-shaped stators and one spherical rotor. And torque is directly output from the surface of the spherical rotor. The structure parameters of SIM are determined based on the design methodology of linear induction motor (LIM), and a finite element model (FEM) is established. Meanwhile, the field-oriented control (FOC) system of SIM is designed, and a multiple physics field co-simulation platform is constituted. By electromagnetic transient simulation and co-simulation, the effectiveness of structure parameters and FOC system are verified systematically. To realize the multi-dimension drive of SIM, the torque model is analyzed, and a multi-DOF drive control strategy is proposed, which is realized by mathematical modeling. The results indicate that SIM can achieve two rotational DOF drive without the angle limitation, and the control system has appropriate dynamic and tracking performances. The design scheme and control strategy proposed are reasonable.